2018
DOI: 10.14254/2071-8330.2018/11-4/13
|View full text |Cite
|
Sign up to set email alerts
|

Сircular economy in the context of alterglobalization

Abstract: This article presents the circular economy as a new economic model, which focuses on the reuse of materials, as well as the creation of additional value through services and intelligent solutions. A number of indicators of the circular economy of EU countries, in particular, import and export of secondary raw materials from EU countries and non-EU countries, are analyzed; the indicator of circularity (9.1%), indicating a significant circular gap-more than 90%. A number of indicators within circular economic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This formulated relevant national priorities for socioeconomic development -increasing level of investment attractiveness, supporting enterprises, promoting job creation, etc. At the same time, implementation of measures to restore economic growth may have potential risks for the country, including excessive resource exploitation and environmental pollution [9]. Thus, in particular, L. Sergienko points out that tendency of worsening environmental problems is mainly due to economic processes and usage of traditional economic model, which is inefficient in terms of negative impact on the environment (and therefore on human life) and cannot be used in the framework of sustainable development [4].…”
Section: Discussionmentioning
confidence: 99%
“…This formulated relevant national priorities for socioeconomic development -increasing level of investment attractiveness, supporting enterprises, promoting job creation, etc. At the same time, implementation of measures to restore economic growth may have potential risks for the country, including excessive resource exploitation and environmental pollution [9]. Thus, in particular, L. Sergienko points out that tendency of worsening environmental problems is mainly due to economic processes and usage of traditional economic model, which is inefficient in terms of negative impact on the environment (and therefore on human life) and cannot be used in the framework of sustainable development [4].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of work [4] took solid waste as the main research object, and they divided the waste into six categories, namely wood, plastic, waste paper, food, textile and rubber. However, through the experiment, it was found that vatyy, [9][10][11] and other scholars, in terms of how to overcome the global waste in global circulation chain, the development of the circular economy globalization, inclusive circulation economy analysis research on the impact of globalization, the economic environment as the prerequisite of the development of international development under the background of the tax environment, increase the green taxes and subsidies to phase out harmful to the environment, and fiscal incentives, VAT reductions and tax relief measures to provide the perfect conditions for the transition to a circular economy [11; 12]. Thus, promoting a circular economy in the context of the formation of circular electronic chains as a solution to overcome global waste.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Presenting circular economy as a new model of production triggers an active scientific and expert discussion as well as EU-wide analytical challenges, aimed at seeking ways to speed up the transition to it. The EU's priority challenge is to find a "circular gap" between EU countries, covering available indicators of circular economy and dividing the countries into "leaders" and "outsiders" (Krysovatyy et al, 2018). In general, across the EU, there is quite a complex picture of building the circular economy, which is difficult to monitor.…”
Section: Literature Reviewmentioning
confidence: 99%